FAKTOR - FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PERAWAT PELAKSANA DALAM MERAWAT PASIEN COVID-19 DI RS X, BANTEN - Hany Wihardja; Yustina Kristine Arif; Rosa Nora Lina (Jurnal Sehat Mandiri, 2021)
Nurse work motivation is defined as an internal and external encouragement for nurses who makes her willing and able to do their jobs. COVID-19 is an infectious disease caused by SARS-CoV-2 which attacks the human respiratory tract and can spread rapidly, with a mortality rate of 5.3%. This quantitative study aims to determine the factors that affect the work motivation of the nurses in caring for COVID-19 patients. This study using a descriptive correlation design with a cross sectional approach. This study involves 58 associate nurse who caring for COVID-19 patients at X Hospital with a total population sampling technique. Nurses' work motivation in caring for COVID-19 patients at RS X is in the moderate category (62-75) using a questionnaire based on Herzberg's motivation theory. Data analysis used the Spearman Rank test, where the results obtained were the influence of age (p value 0.023), marital status (p value 0.028) and work environment (p value 0.011) with work motivation.The conclusion of this study is the motivation of nurses while caring COVID-19 patients are influenced by factors of age, marital status and work environment such as the availability of policies and personal protective equipment. Recommendation that can be given to increase the work motivation of nurses at X Hospital by disseminating information about hospital policies in handling nurses infected with COVID-19, COVID-19 management, modes of transmission and other actual information so as to reduce nurse anxiety.